Floating treatment wetland as an alternative for water quality improvement: A preliminary study - Nur Asmaliza M.N.; Lariyah M.S.; Kok K.H.; Humaira H.S.; Hidayah B. (Trans Tech Publications Ltd, 2023)
Floating treatment wetland (FTW) is one of green innovation in order to enhance water quality as an alternative treatment for water quality improvement. The aim of this study is to identify the capability of floating wetland to remove stormwater pollutant in the river. The lab scale floating treatment wetlands were set up using three different sizes of the floating system with floating mat that made from plastics. Water quality samplings had been conducted starting from 4 December 2012 until 14 December 2012 to evaluate the performance for floating treatment wetland. The results indicate the removal efficiency gradually increased with the hydraulic retention time for water quality parameters such as Total Suspended Solid (TSS), Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Phosphorus (TP) and Total Nitrogen (TN) with a range of removal efficiency from 70% to 100%, -5.55% to 88.9%, 9.1% to 68.2%, -8.3% to 63% and 31.4% to 70.3% respectively. © (2014) Trans Tech Publications, Switzerland.